2016
DOI: 10.1177/0004944116667620
|View full text |Cite
|
Sign up to set email alerts
|

Should I stay or should I go? Resilience as a protective factor for teachers’ intention to leave the teaching profession

Abstract: Teacher attrition is a current issue in Australia and other economically developed countries, with up to 50 per cent of teachers resigning from teaching within the first five years. Teacher attrition is widely considered to impact negatively on student achievement and the school. The present study of 160 Australian primary and secondary teachers who have been in the profession for up to 10 years investigates whether teachers’ generalised resilience is associated with their intention to leave the teaching profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 44 publications
1
69
0
3
Order By: Relevance
“…In general, research studies suggest that teaching has traditionally been considered a respected profession, particularly a suitable job for women. Yet increasingly teachers are not held in such high regard [16,17]. Studies have shown that those entering the teaching profession have not been the most academically motivated or accomplished students [3,17].…”
Section: Review Of Factors Influencing Teacher Recruitment Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In general, research studies suggest that teaching has traditionally been considered a respected profession, particularly a suitable job for women. Yet increasingly teachers are not held in such high regard [16,17]. Studies have shown that those entering the teaching profession have not been the most academically motivated or accomplished students [3,17].…”
Section: Review Of Factors Influencing Teacher Recruitment Literaturementioning
confidence: 99%
“…Research has also shown that pay and work conditions have been identified as factors that dissuade individuals from becoming teachers [18]. Many of those choosing to teach have been able to overlook some negative aspects like low pay and difficult work conditions because they considered teaching to be a calling, citing altruistic or social utility motivations [16,19]. Factors that researchers have identified as impacting whether or not an individual will enter the teaching profession are presented in Table 1.…”
Section: Review Of Factors Influencing Teacher Recruitment Literaturementioning
confidence: 99%
“…So, recruiting and retention of quality teachers is one of the top priorities of managers in any education system. But global statistics show high rate of teachers' turnover (Arnup & Bowles, 2016;Dassa & Derose, 2017;Hong, 2010) for some reasons such as job stress, unfavorable working conditions (Kyriacou, 2001;Skaalvik & Skaalvik, 2011; cited by Arnup & Bowles, 2016), high workload, lack of school support and issues related to students' behavioral management (Kyriacou, 2001; cited by Arnup & Bowles, 2016). Regarding the negative effects and consequences of quitting, one of the major concerns of managers and researchers is to find affecting factors of teachers intention to stay.…”
Section: Introductionmentioning
confidence: 99%
“…vynárajúcej sa dospelosti (Arnett, 2000;Somerville, 2013) a môže vykazovať známky zvýšenej vývinovo -podmienenej emočnej lability. Najvyšší rozdiel (d = 0,472) evidujeme v dimenzii odolnosť voči záťaži, čo je oblasť, ktorú vnímame ako jednu z kľúčových práve v období tranzitu do praxe, ktorý je spojený so zvýšenou pracovnou záťažou a profesijným stresom učiteľov (Arnup & Bowles, 2016).…”
Section: Diskusiaunclassified